PENGEMBANGAN SISTEM ERP HRD PT QUEEN NETWORK NUSANTARA MENGGUNAKAN FRAMEWORK REACT - Afriansyah, Aidil; Annisa, Resty (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
In the current industrial era 4.0, of course you are no stranger to things related to information technology. Web technology is currently widely used, especially to facilitate the work of an agency or company. PT. Queen Network Nusantara requires a system that can be integrated and monitors all company resources. The system that can meet the needs of this company is an ERP (Enterprise Resource Planning) system. PT. Queen Network Nusantara requires an ERP system that can manage employee data. Building an HRD ERP system website that is used to manage employee data. System development uses the Extreme Programming method with an overview of the QNN HRD ERP system and web-based QNN HRD ERP attendance with one of its features is monitoring employee attendance and employee attendance online. Testing the QNN HRD ERP system was carried out using the System Usability Scale (SUS) method with a score of 76 and can be classified as Acceptable and functional testing using the Black Box Testing method with the result that the system is running well. The developed system is expected to be able to automate many HR processes and make employee management more efficient and help organizations track employee performance.